The Cooperative and Conflict Mechanism of Economic Diplomacy in International Relations: A Cognitive Approach - Achour, Salime (Journal of Legal Studies and Researches, 2023)
This research paper focuses on how economic power and its tools play a pivotal role in international policy besides military power, and that international relations are either cooperative or conflict relations, or both, and economic diplomacy is the use of all the available potentials and economic capabilities of the country, whether cooperatively through aid ... Or use them as economic sanctions... Adapt to the goals of the state.